Gender differences among Alaska Native people seeking alcohol withdrawal treatment. Issue 2 (2nd April 2016) - Bear, Ursula Running; Beals, Janette; Novins, Douglas K.; Manson, Spero M.
ABSTRACT: Background : Few studies focus on gender differences among patients who utilize detoxification services; even fewer focus on detoxification for Alaska Native people. This analysis focused on gender differences at admission among a sample of Alaska Native patients seeking alcohol withdrawal treatment. Methods : The sample included 383 adult Alaska Native patients admitted to an inpatient alcohol detoxification unit during 2006 and 2007. Logistic regression was used to estimate unadjusted and adjusted associations with gender. Results : Women were 88% more likely to have stable housing than men (odds ratio [OR] = 1.88, 95% confidence interval [CI] = 1.15, 3.05, P = .01). Women were 87% less likely to be seasonal workers (OR = 0.13, 95% CI = 0.03, 0.48, P = .003) and 50% less likely than men to be seeking employment (OR = 0.50, 95% CI = 0.29, 0.84, P = .01) at admission. Women had more than 5 times the odds of having children in the home at admission (OR = 5.64, 95% CI = 3.03, 10.56, P < .001) and almost 3 times the odds of experiencing physical abuse than men (OR = 2.96, 95% CI = 1.31, 6.66, P = .01). Additionally, women were 50% less likely to accept a referral to substance abuse treatment following detoxification (OR = 0.50, 95% CI = 0.30, 0.83, P = .01). Conclusions : The study found significant differences based upon gender. For instance, women are in need of services that accommodate women with children and services that address histories of physical abuse. Conversely, men are in need of housing and employment opportunities. Post detoxification follow-up, case management, and transition to care should include gender as a factor in treatment planning.